Ionic transport properties improvement of a new cation-exchange membrane containing functionalized CNT as a clean technology for refining of saline-liquids. Issue 8 (3rd April 2021) - Heidary, Farhad; Khodabakhshi, Ali Reza; Ghanbari, Davood
ABSTRACT: In the present research, a novel kind of homogeneous cation-exchange membranes were provided by solution casting technique via blending of sulfonated polyvinylchloride (SPVC) and sulfonated poly phenylene oxide (SPPO). The performance of the membranes was evaluated by membrane potential, areal resistance, transport number, ionic permeability, ion-exchange capacity, fixed ion concentration, energy consumption (EC), current efficiency, mechanical properties, membrane oxidative stability, water contact angle and water content tests. The microstructures of the membranes were investigated by scanning electron microscopy. Membrane with 70:30 (w/w) composition (SPPO: SPVC) exhibited suitable efficiency, mechanical strength and oxidative stability in comparison with other samples in this study. Also, amino groups have been successfully attached to the multi-walled carbon nanotubes (MWCNTs) structure and the modified MWCNTs were selected as filler additive. The results revealed that a series of membranes with improved transport properties, hydrophilicity and EC can be prepared with the polymeric matrix-containing aminated-MWCNTs. GRAPHICAL ABSTRACT: UF0001